Creativity of students in favour of their entrepreneurial intentions: empirical evidence from Poland - Wach, Krzysztof; Bilan, Svitlana (Creativity Studies, 2023)
The article aims to empirically verify the impact of creativity on students’ entrepreneurial intentions using a theoretical framework of the enhanced theory of planned behaviour of Icek Ajzen. The primary research tool was a survey conducted among students (n = 719) of several universities in Kraków, Poland. Statistical calculations of multiple regression positively verified the hypothesis that students’ creativity strengthens their entrepreneurial intentions to start their own business. The model has a strong predictive power (R2 = 65.3%). University teaching should be focused more on unleashing students’ creativity to boost entrepreneurial intentions of students, then to transpose into startups, and then eventually to support the competitiveness of the economy. This article’s novel contribution is to confirm that social norms in Poland do not play an essential role in stimulating entrepreneurial intentions despite numerous affirmations to this factor in other countries.